Double aneuploidy: A unique case of trisomy 21 with XYY - Tiwari, Abhinav; Trivedi, Pranay; Sakhare, Wrunda; Thakur, Nohar Singh; Chandramohan, G. Malini (Indian Journal of Child Health, 2020)
The double aneuploidy or two chromosomal abnormalities occurring in an individual are relatively uncommon. It mainly arises due to non-disjunction at either first or second meiotic division. The double aneuploidy 48, XXY, +21 was described for the 1st time in 1959, and the incidence is reported to be 0.4–0.9/10,000 male births. Chromosomal abnormalities are seen in 1–2% of live births. We report a case of newborn with the clinical features of Down’s syndrome, the most common aneuploidy and genetic cause of moderate intellectual disability. Cytogenetic analysis showed karyotype of 48, XYY, + 21. Our case had double aneuploidy (48, XYY, +21) with congenital heart disease and hypothyroidism.